Kinsey [videorecording (DVD)] - Condon, Bill, 1955-; Neeson, Liam; Linney, Laura; O'Donnell, Chris (Distributed by 20th Century Fox Home Entertainment, 2005)
Kinsey is a portrait of a man driven to uncover the most private secrets of the nation, and journey into the mystery of human behavior. His 1948 book Sexual Behavior in the Human Male irrevocably changed American culture and created a media sensation.